Pengembangan Kemampuan Berpikir Kritis Siswa melalui Pembelajaran Matematika Open-ended di Sekolah Dasar - Ifada Novikasari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
The aim of learning not only for fundamental principles mastery in the field of skill, but also develop which are positive attitude, research and invention with problem solving from their ability. The mathematics study in elementary school, supposed happen reinvention. Activity open-ended can bring student in answer problem with many manner and may be also many answers (true) so that invite intellectual potential and student experience in course to find something new.Â